2014
DOI: 10.2138/am-2015-4773
|View full text |Cite
|
Sign up to set email alerts
|

Megacrystic zircon with planar fractures in miaskite-type nepheline pegmatites formed at high pressures in the lower crust (Ivrea Zone, southern Alps, Switzerland)

Abstract: Trace element, Hf, and O isotopic composition and U-Pb geochronological data are reported for zircon megacrysts found in miaskitic (zircon, biotite, plagioclase-bearing) nepheline syenite pegmatites from the Finero complex in the Northeastern part of the Ivrea-Verbano Zone, southern Alps. Zircon from these pegmatites was reported to reach up to 9 cm in length and is characterized by ~100 μm spaced planar fractures in different directions. Small volumes of these highly evolved alkaline melts intruded into the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 49 publications
(55 reference statements)
5
59
0
Order By: Relevance
“…7 of Ewing et al 2013). The sporadic influx of fluids at 220-200 Ma is consistent with the occurrence of episodic mantle-derived magmatism and associated metasomatism in the northern IVZ from ~220 to 190 Ma (Grieco et al 2001;Morishita et al 2008;Schaltegger et al 2015;Stähle et al 1990), as described in detail in Sect. 2.…”
Section: Constraints On the Permian To Jurassic Thermal Evolution Of supporting
confidence: 78%
See 2 more Smart Citations
“…7 of Ewing et al 2013). The sporadic influx of fluids at 220-200 Ma is consistent with the occurrence of episodic mantle-derived magmatism and associated metasomatism in the northern IVZ from ~220 to 190 Ma (Grieco et al 2001;Morishita et al 2008;Schaltegger et al 2015;Stähle et al 1990), as described in detail in Sect. 2.…”
Section: Constraints On the Permian To Jurassic Thermal Evolution Of supporting
confidence: 78%
“…Episodic Triassic to Jurassic mantle-derived magmatism in the northernmost IVZ is recorded by alkaline dikes and pegmatoids intruding the Finero peridotite, with zircon UPb ages ranging between ~190 and 225 ± 13 Ma for these localised intrusions (Schaltegger et al 2015;Stähle et al 1990). Associated Late Triassic metasomatic events are also recorded in this area.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northeastern and southwestern parts of the Ivrea Zone, some samples show an age generation < 220 Ma (Zanetti et al 2013;Schaltegger et al 2015;Langone et al 2017) we have found no evidence for that in Val Strona di Omegna (Fig. S9 Online Resource 3).…”
Section: Implications For the Interpretation Of The Metamorphic Evolumentioning
confidence: 63%
“…The main intrusive phase has been dated on zircon by Peressini et al (2007) at 288 ± 4 Ma, with locally earlier magmatic activity at ~ 295 Ma (Sinigoi et al 2011) and 314 ± 5 Ma (Klötzli et al 2014). In the northern part of the Ivrea Zone, the Finero mafic-ultramafic body is characterised by a range of Permian U-Pb zircon dates as well as younger zircon intrusion ages of 232 ± 3 Ma and late fluid-related recrystallisation between ~ 220 and 200 Ma (Zanetti et al 2013;Schaltegger et al 2015;Langone et al 2017).…”
Section: Geological Settingmentioning
confidence: 99%